2023
DOI: 10.3389/fcvm.2023.1127653
|View full text |Cite
|
Sign up to set email alerts
|

Carotid atherosclerotic plaque segmentation in multi-weighted MRI using a two-stage neural network: advantages of training with high-resolution imaging and histology

Abstract: IntroductionA reliable and automated method to segment and classify carotid artery atherosclerotic plaque components is needed to efficiently analyze multi-weighted magnetic resonance (MR) images to allow their integration into patient risk assessment for ischemic stroke. Certain plaque components such as lipid-rich necrotic core (LRNC) with hemorrhage suggest a greater likelihood of plaque rupture and stroke event. Assessment for presence and extent of LRNC could assist in directing treatment with impact upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…CACSNet with EfficientNet-B4 backbone achieved a JI of 0.595, DSC of 0.722, precision of 0.749, and recall of 0.756. Several investigations of CAC segmentation in images other than PRs using deep learning models have been conducted 22 24 , 55 57 . The deep learning models achieved a DSC of 0.795 in CT angiographic images 23 , a DSC of 0.9381 in ultrasound images 24 , and a DSC of 0.78, precision of 0.76, and recall of 0.8 in MR images 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CACSNet with EfficientNet-B4 backbone achieved a JI of 0.595, DSC of 0.722, precision of 0.749, and recall of 0.756. Several investigations of CAC segmentation in images other than PRs using deep learning models have been conducted 22 24 , 55 57 . The deep learning models achieved a DSC of 0.795 in CT angiographic images 23 , a DSC of 0.9381 in ultrasound images 24 , and a DSC of 0.78, precision of 0.76, and recall of 0.8 in MR images 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations of CAC segmentation in images other than PRs using deep learning models have been conducted 22 24 , 55 57 . The deep learning models achieved a DSC of 0.795 in CT angiographic images 23 , a DSC of 0.9381 in ultrasound images 24 , and a DSC of 0.78, precision of 0.76, and recall of 0.8 in MR images 22 . Therefore, compared with previous studies performed on other modalities, CACSNet demonstrated comparable segmentation performance for CACs on PRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations